The Influence of Traditional Exports on Economic Growth in Tanzania: The VECM Analysis - Chindengwike, James Daniel (Journal of Business and Management, 2023)
Background: Tanzania, like other developing countries, sees commerce as one of the most important tools for the country’s growth and progress. Given that export is one of Tanzania’s primary economic sectors, several empirical studies on the relationship between international commerce and the country’s economic growth have been conducted. Objectives: The study looked primarily at the influence of traditional exports as the primary independent variable. Furthermore, the Natural Logarithm of Terms of Trade (TOT), the currency rate, and Foreign Direct Investment (FDI) are control variables, whereas GDP is the dependent variable. Methods: The research employed time-series data from the World Bank, the Bank of Tanzania (BOT), and the United Nations Conference on Trade and Development (UNCTAD) that spans 31 years from 1991 to 2021 based on the Vector Error Correlation Model (VECM). Results: The findings revealed a link between Tanzania’s economic growth and traditional exports, trade terms and currency rate. Furthermore, studies have found a negative and substantial association between exchange rates and economic growth in both the short and long run. Conclusion: The findings indicated that trade terms and traditional exports had a favorable and considerable influence on economic growth in the short run. In the long run, traditional exports and FDI had a negative and positive influence on economic growth, but trade terms had a considerable and positive effect. As a result, the study argues that Tanzania’s government should prioritize export promotion measures above traditional exports to accelerate Tanzania’s economic growth. The government should prioritize the establishment of factories that will add value to traditional export items